Georgia Architectural and Historic Properties Survey of Quitman [272] Old Madison Road, Valdosta, Ga. December 1980. - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Quitman [272] Old Madison Road, Valdosta, Ga. December 1980. Large two story rectangular plan house. Multi-gabled roof with brackets and cut and return corners. Shed porch (screened). Clapboard siding. Sash windows with 2/2 lights. Shutters. Large interior chimneys. Five sided bay at right. Set on a residential street in the midst of more modern houses. Good condition. Date of Construction: c. 1915-1920. Not really significant architecturally because it is not extremely innovative or unusual, but certainly adds charm to this area.
Georgia Architectural and Historic Properties Survey of Quitman [272] Old Madison Road, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.31 MB (1,379,306 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)